The provision of the elementary core French program in small rural schools in Newfoundland and Labrador - Ryan, Margaret Mary, 1962- (1996)
Thesis (M.Ed.)--Memorial University of Newfoundland, 1996. Education Bibliography: leaves 88-95. This thesis has investigated the provision of the Elementary Core French Program in small rural schools in Newfoundland and Labrador. The implementation of the communicatively based program Aventures in our province in the 1980s required a shift in teaching methodology and a teacher who was comfortable in the language and who fully understood the philosophy of communicative language teaching. I was interested in examining how effective this implementation has been in the small rural schools in the province. Frequently, teaching in a multi-graded setting, the teacher in a small school is responsible for all subjects, including French, at different grade levels. My study sought to develop a profile of the Elementary Core French Program in these small schools. -- The review of the literature was done in two domains: (1) second-language teaching and learning, and (2) rural education. A survey questionnaire was developed from the themes and concerns prevalent throughout the literature and administered to the total accessible population (schools with student populations of 100 or less which offered elementary core French) in May of the 1994-95 school year. Data gathered via the completed questionnaires was analyzed using both descriptive and inferential statistics. The descriptive statistics used mainly frequency distributions and means, served to establish an overall picture of the Elementary Core French Program in small rural schools with respect to qualifications of teachers, resources available, support for the program, and use of communicative strategies. The inferential statistics consisting of chi-squares provided several significant relationships between teacher preparation in French and variables such as use of communicative strategies and proficiency levels. -- The results suggest that teachers in small rural schools are not adequately prepared to provide an effective Elementary Core French Program. Thus, the program objectives cannot be achieved. In addition, the findings of this research provide the basis for several recommendations which address the problems with elementary core French in small rural schools.